2019
DOI: 10.1002/sctm.19-0183
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Therapies for Alveolar Bone and Periodontal Regeneration: Concise Review

Abstract: Current regenerative strategies for alveolar bone and periodontal tissues are effective and well adopted. These are mainly based on the use of a combination of synthetic/natural scaffolds and bioactive agents, obviating the incorporation of cells. However, there are some inherent limitations associated with traditional techniques, and we hypothesized that the use of cell-based therapies as part of comprehensive regenerative protocols may help overcome these hurdles to enhance clinical outcomes. We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Several studies have demonstrated that transplantation of in vitro ‐amplified PDLSCs and scaffolds into the defect could potently improve the repair of periodontal tissue structures in animal models 11‐13 . However, traditional tissue engineering often uses trypsin digestion to obtain individual cells, which not only loses the extracellular matrix (ECM) components but also destroys the biological connection between cells and reduces cell utilization efficiency 14,15 . In order to solve these limitations, Okano and coworkers developed cell‐sheets technology 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that transplantation of in vitro ‐amplified PDLSCs and scaffolds into the defect could potently improve the repair of periodontal tissue structures in animal models 11‐13 . However, traditional tissue engineering often uses trypsin digestion to obtain individual cells, which not only loses the extracellular matrix (ECM) components but also destroys the biological connection between cells and reduces cell utilization efficiency 14,15 . In order to solve these limitations, Okano and coworkers developed cell‐sheets technology 16 .…”
Section: Introductionmentioning
confidence: 99%
“…While this strategy has not yet been implemented in the clinic, several clinical studies have been conducted utilizing exogenous stem cells although few have investigated BMSC stem cell based treatment options. Rather dental derived cell options have been employed for dental, periodontal, gingival and bone regeneration clinical trials, including dental pulp, gingival and periodontal ligament derived stem/progenitor cells [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ].…”
Section: Bmsc Treatment For Bone Related Skeletal Diseases/disordementioning
confidence: 99%
“…There are limited clinically available therapeutic treatments for periodontitis apart from mechanical or surgical debridement with grafting procedures. Therefore stem cell based approaches have been explored to improve functional regeneration of lost bone [ 182 ]. In a phase I/II clinical trial based on preclinical studies, autologous BMSC combined with platelet-rich plasma, and a biodegradable 3D woven-fabric composite scaffold showed efficacy, stability and safety for periodontists over a 36 month period [ 54 ].…”
Section: Bmsc Treatment For Bone Related Skeletal Diseases/disordementioning
confidence: 99%
“…In quest of a treatment approach with a consistent and clinical worthwhile benefit, tissue engineering (TE), based on the triad of mesenchymal stem cells (MSCs), biomolecules and scaffolds have been considered as an alternative for periodontal regeneration (Hynes et al, 2012). Mesenchymal stem cells can be expanded ex vivo to several millions of cells from a small tissue biopsy (Bakopoulou et al, 2017), or they can be minimally manipulated in the form of micro‐grafts (Trovato et al, 2015), having practical values as culture expanding procedures are avoided (Moreno Sancho et al, 2019). Successful MSC‐based therapies necessitate the selection of the most suitable cell source for the intended clinical application (Egusa et al, 2012), and autologous alveolar bone marrow MSCs (a‐BMMSCs) were elected for current use (Mason et al, 2014; Brennan et al, 2017; Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%